The role of glycans in health and disease: Regulators of the interaction between gut microbiota and host immune system - Crouch, LI (2024)
The human gut microbiota is home to a diverse collection of microorganisms that has co-evolved with the host immune system in which host-microbiota interactions are essential to preserve health and homeostasis. Evidence suggests that the perturbation of this symbiotic host-microbiome relationship contributes to the onset of major diseases such as chronic inflammatory diseases including Inflammatory Bowel Disease. The host glycocalyx (repertoire of glycans/sugar-chains at the surface of gut mucosa) constitutes a major biological and physical interface between the intestinal mucosa and microorganisms, as well as with the host immune system. Glycans are an essential niche for microbiota colonization and thus an important modulator of host-microorganism interactions both in homeostasis and in disease. In this review, we discuss the role of gut mucosa glycome as an instrumental pathway that regulates host-microbiome interactions in homeostasis but also in health to inflammation transition. We also discuss the power of mucosa glycosylation remodelling as an attractive preventive and therapeutic strategy to preserve gut homeostasis.